The technology tasks fit, its impact on the use of information system, performance and users' satisfaction. Issue 3 (15th June 2020) - Ratna, Silvia; Nayati Utami, Hamidah; Siti Astuti, Endang; Wilopo,; Muflih, Muhammad
Abstract : Purpose: Find out how the employees' performance on the implementation of the hotel reservation information system. Therefore, this paper aims to examine the effect of the task-technology fit (TTF) on the use of information systems, as well as its effect on user performance and satisfaction. Design/methodology/approach: This research type is explanatory research. In explanatory research, the aim is to provide an explanation related to the causal relationship between variables and hypothesis testing. The unit of analysis adopted in this study is the individual of the front office employees who use the star hotel reservation information system in South Kalimantan Province (the population is 239, and the taken are 150 samples, based on the number of indicators multiplied 5). Findings: The higher the TTF, the higher the level of using information systems. The higher the use level of information systems, the higher the information systems user performance and vice versa in which the higher the user's performance, the more increase the use of information systems. On the other hand, this study found that the use of information systems and user performance has no significant effect on user satisfaction. Originality/value: The novelty in this study is shown in the influence between performance variables on the usage and the usage variables on the users' performance. This study examines the importance of reciprocal usage and user performance relationships based on previous research studies that examine the relationship and that information technology (IT) usage will affect user performance. In addition, the users' performance will affect the users' behavior in using IT.